Medicinal Plants Their importance in Pharmaceutical Sciences - Kuntal Dasa (Kalyani, 2013)
Medicinal plants have played a vital role in many ancient traditional systems of medication in world wide. Traditionally,people are believed on plant based medicine for their primary health care